O direito do consumidor à efetiva proteção do armazenamento de dados relativo aos negócios jurídicos firmados no ambiente eletrônico - Matsuda, Marcelino Sato (2017)
The facility of new equipments associated with the different ways people communicate has changed social behavior and the way of practicing the legal business. In 2014, the Civil Mark of Internet took effect, without taking care of the storage of legal business data nor the information content to be stored. Which leads us to ask: How to guarantee the effectiveness of consumer rights at the necessary moment to prove the legal business performed through information technologies? In order to solve this question, we start from general assumptions applied to consumer rights, the relevant legislation to the Internet, the law projects related to e-commerce and the prescription of the Civil Code to show the necessity of storing the legal business information in log files by 10 years. The present study has importance for the effectiveness of consumer protection projected over time and in the rescue of information. Furthermore, we believe that this study may contribute with other studies on the same matter, since information technology is a matter quite discussed nowadays